THE ROLE OF DIGITALIZATION IN THE FIGHT AGAINST CORRUPTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Digital technologies are becoming increasingly of main importance and provide a growing influence on public life. It impacts corruption and its counteraction across various sectors of society. At the current stage of society development, there are high expectations for combating this social phenomenon, and the advancement of information technologies and digitalization presents significant potential and prospects in the fight against corruption. This article examines possible trends and perspectives for utilizing digital tools in the fight against corruption, as well as identifying risks and new threats related to corruption in the context of digitalization processes in public administration and the digitization of services provided to citizens.